A History of Copper and Wire Drawing: The Past 11,000 Years And Beyond - H. P{ops (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
This paper summarizes important developments that have occurred in the mining and subsequent production of copper into rod and wire from 9000 B.C. until the present time. Principles and practices associated with continuous rod production are discussed from a metallurgical perspective, and include the effects of oxygen content and impurities. A brief historical review is also given of important wire drawing events dating back thousands of years. Finally, predictions concerning the future of the wire and cable industry are presented with particular emphasis upon copper wire, technology in this market, and competitive materials.